Urban transportation conditions from the metropolitan area of Kuala Lumpur that will impact and Endanger Putrajaya’s sustainability plan - Bonasif, Jorge (International Conference “Environmental Engineering”, 2017)
There is a growing demand for mobility and accessibility from the Klang Valley (The Greater Kuala Lumpur) into the city of Putrajaya. Putrajaya is the federal administrative Capital of Malaysia, conceived as the first sustainable intelligent city-garden. The public connectivity in Kuala Lumpur is mainly centralized with the RR (Rapid rail) integrated by the Light Rail Transit (LRT) and the MRT (Mass Rapid Transit) with connections by bus to the peripheral zones. However the primary mode of transportation is still private vehicles such as cars and motorcycles, with an increased use from 458,294 in 2006 to 628,239 in 2012. In 1990, these numbers increased from 247 vehicles per 1,000 persons to 546 and 994 vehicles per 1,000 persons in 1996 and 2002 respectively, beyond the national level per 1,000 population of 91 vehicles in 1990, 133 in 1996 and 210 vehicles in 2002 incrementing the heavily congested conditions existent in the traffic grid, thus also affecting the connection with Putrajaya (Kuala Lumpur Structured Plan 2020). This paper highlights the necessity for a closer examination to some of the factors that exert influence on the motivation of the preference in the use of private transportation in detriment of the existent public urban network that will affect and endanger the sustainable nature of Putrajaya. The primary methodology used is the consultation of available literature, newspapers, published reports, and interview with experts. A secondary source is the observation in situ to help support the conclusions. The constant growth on the demand for private transportation in the population is hypothesized to be directly positively correlated to a very ingrained tradition, unchangeable weather conditions and the unreliable connectivity. These factors directly affect the lack of incentives to improve existent public transportation from Klang Valley to Putrajaya.